Japanese relations with Vietnam, 1951-1987 - Shiraishi, Masaya (Southeast Asia Program series, 1990)
A chronological overview from the end of World War II to 1990. This work gives a broad analysis of the major changes, strategies, and situations that helped shape diplomatic and economic relations between the two nations.